OC-158 Endogenous production of antibiotics by mesenchymal stem cells and the potential value in crohn's fistula healing. (28th May 2012) - Meran, L; Garavaglia, M; Heeb, S; Bayston, R; Richards, B; Ashraf, W; Rose, F; Shakesheff, K; Hawkey, C
Abstract : Introduction: Potent effects of human mesenchymal stem cells (MSCs) on immune responses have been demonstrated in vitro studies and animal models, encouraging further investigations into their clinical value. Studies of MSCs in fistula healing have emphasised the immunosuppressive mechanisms of action however, there has been little focus on their antibacterial activity in this setting. We report here on the antibacterial effects of MSCs against Adherent Invasive Escherichia coli (AIEC), reference strain LF82. Methods: Cultured human bone marrow derived MSCs were plated at a density of 5×10 4 cells per square centimetre in 24 well plates and allowed to adhere overnight. Confluent MSCs were preincubated for 1-day with fresh culture medium alone or medium supplemented with 1 ng/ml TNFα. Cells of passage numbers 4–9 were co-cultured with a calculated 300 Colony Forming Units of AIEC strain LF82 and incubated for 6 h in a humidified CO2 incubator. Aliquots of the infected medium were taken from each well and plated on LB-agar plates and colonies were counted after overnight incubation. Comparisons were made with aliquots from inoculated wells containing cells that were pre-stimulated with TNFα, in addition to wells that did not contain mesenchymal stem cells. Data analyses were performed using the SPSS statistical package (V.19.0). Results: Each of the wells under test conditions was inoculated with 379±98 CFU at the start of the co-culture time period. In the absence of mesenchymal stem cells, the number of LF82 CFUs in mesenchymal stem cell culture medium had risen to a mean (±SD) of 1780±319 [n=3], after 6 h. In the presence of passage-4 MSCs, the number of LF82 CFU was significantly reduced by 81.2%, to 335±61 [n=3] (p<0.05). When MSCs were prestimulated with TNF, there was a further reduction of CFU levels to 15±6 [n=3]. When cells of higher of passage numbers were used, the effects both in the presence and absence of TNF prestimulation diminished such that by passage-8, there was no significant inhibition of bacterial growth. Conclusion: The antibacterial properties of MSCs alongside their tissue regenerative potential make them ideal candidates for use in therapeutic strategies for fistula healing. This study demonstrates that in a proinflammatory environment, MSCs enhance bacterial clearance of AIEC. These findings encourage further evaluation of the antimicrobial effector function of MSCs against other strains suspected to participate in the pathogenesis of Crohn's disease. Competing interests: None declared.